Study Of The Impact Of Changing Patterns From Cocoa Farming To Corn Business On Farmers' Socio-Economic - Nuddin, Andi; Kalsum, Putri Umi; Nurhaeda, Nurhaeda (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2024)
Cocoa farmers in Matangnga subdistrict, Polewali Mandar district, specifically in Matangnga subdistrict, have been producing cocoa for decades. However, in the last 2 years, many cocoa farmers have switched to corn farming, even though cocoa is Indonesia's mainstay commodity and the 3rd largest cocoa producer in the world. This research aims to find out the perceptions of cocoa farmers regarding changes in farming patterns from cocoa to corn, to find out the impact on farmers' socio-economic conditions and to find out how cocoa farmers' income is after changing farming patterns to corn in Matangnga District, Polewali Mandar Regency. The sample determination method in this research uses purposive sampling, which is namely a technique that is based on certain considerations made by the researcher based on previously known characteristics or traits of the population, then the researcher determines based on his considerations. The data collection methods are observation, interviews and documentation. The data analysis method used is qualitative descriptive data analysis, namely in the form of a collection of words taken from interviews (questionnaires) given to farmers regarding cocoa and corn farming income analysed using the farming income analysis method.